Nurse Management in Dialysis Center in Covid-19 Time − Single-Center Experience - Bosiljka Devčić; Ivan Bubić; Vesna Babić; Božidar Vujičić; Sanjin Rački (Acta Clinica Croatica, 2021)
COVID-19 infection in patients treated in dialysis centers is a particular challenge given that there is a significantly increased risk of transmitting the infection to medical staff, other staff of the institution, other patients, and family members of the patients. The purpose of our work is to share our experiences in the implementation of preventive and epidemiological measures with reference to patients on a chronic outpatient hemodialysis program. Nurses play an important role in education and caring for the dialysis patient.